Knowledge engineering, machine learning and lattice computing with applications : 16th International Conference, KES 2012, San Sebastian, Spain, September 10-12, 2012, Revised Selected Papers - Toro, Carlos; Howlett, Robert J.; Jain, Lakhmi C.; Grana, Manuel (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the 16th International Conference on Knowledge-Based and Intelligent Information and Engineering Systems, KES 2012, held in San Sebastian, Spain, in September 2012. The 20 revised full papers presented were carefully reviewed and selected from 130 submissions. The papers are organized in topical sections on bioinspired and machine learning methods, machine learning applications, semantics and ontology based techniques, and lattice computing and games.